Uppfödning av gyltor till hållbara suggor - Hidås, Lina (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2010)
Half of Sweden’s 140 000-150 000 sows are culled and replaced by 75 000 gilts annually. Culling of old sows is necessary and allows new breeding material to enter the herd. However, many of the culled sows are young, and have not yet become profitable at the time for culling. Therefore, it is an important question for the pig industry, how to raise gilts to sows with a high and sustainable production level.